Communication and Affective Synchrony between Parents and Their Children with Autism during a Multimodal Communication Parent-Coaching Intervention. Issue 2 (3rd April 2022) - Ganz, Jay B.; Liew, Jeffrey; Yllades, Valeria; Liao, Ching-Yi; Luo, Wen; Hong, Ee Rea; Yoro, Amara J.; Rodriguez, Daira; Clark, Shannon; Stein, Kaitlyn; Ura, Sarah K.
Abstract: The present study aims to increase diversity in autism research and reduce the barriers to support services for children with ASD through a parent-coaching intervention delivered using telepractice. Specifically, the effects of the intervention on communication and affect for both the parent and child with autism were evaluated longitudinally across 8 time points or sessions. Using a quasi-experimental design, without a control group, findings highlight the parent-child dyadic synchrony and responsiveness in affective and communicative competence in the home via a multimodal parenting intervention. Thus, verbal, and affective communication skills are promising targets for future naturalistic intervention strategies with parents or caretakers. Moreover, findings highlight that access to interventions could be increased to diverse and under-represented populations by leveraging telepractice approaches.